On the reform of the first philosophy and the notion of substance - von Leibniz, Gottfried Wilhelm; Másmela Arroyave, Carlos (Estudios de Filosofía, 1992)
The notion of substance, as I propose it, is so fruitful that primary and original truths emerge from it and, in reality, referring to God, souls, and the nature of bodies (that is, all this and their realms). They are truths known in part but little proven; partly unknown until now, however, of great significance for other sciences.